Resource-use efficiency explains grassy weed invasion in a low-resource savanna in north Australia - Ens, Emilie; Hutley, Lindsay B.; Rossiter-Rachor, Natalie A.; Douglas, Michael M.; Setterfield, Samantha A. (Frontiers in Plant Science, 2015)
Comparative studies of plant resource use and ecophysiological traits of invasive and native resident plant species can elucidate mechanisms of invasion success and ecosystem impacts. In the seasonal tropics of north Australia, the alien C4 perennial grass Andropogon gayanus (gamba grass) has transformed diverse, mixed tree-grass savanna ecosystems into dense monocultures. To better understand the mechanisms of invasion, we compared resource acquisition and usage efficiency using leaf-scale ecophysiological and stand-scale growth traits of A. gayanus with a co-habiting native C4 perennial grass Alloteropsis semialata. Under wet season conditions, A. gayanus had higher rates of stomatal conductance, assimilation, and water use, plus a longer daily assimilation period than the native species A. semialata. Growing season length was also ~2 months longer for the invader. Wet season measures of leaf scale water use efficiency (WUE) and light use efficiency (LUE) did not differ between the two species, although photosynthetic nitrogen use efficiency (PNUE) was significantly higher in A. gayanus. By May (dry season) the drought avoiding native species A. semialata had senesced. In contrast, rates of A. gayanus gas exchange was maintained into the dry season, albeit at lower rates that the wet season, but at higher WUE and PNUE, evidence of significant physiological plasticity. High PNUE and leaf 15N isotope values suggested that A. gayanus was also capable of preferential uptake of soil ammonium, with utilization occurring into the dry season. High PNUE and fire tolerance in an N-limited and highly flammable ecosystem confers a significant competitive advantage over native grass species and a broader niche width. As a result A. gayanus is rapidly spreading across north Australia with significant consequences for biodiversity and carbon and retention.